Patterns of democratic backsliding in third-wave democracies: a sequence analysis perspective. Issue 2 (17th February 2023) - Wunsch, Natasha; Blanchard, Philippe
ABSTRACT: Democracy has come under pressure worldwide, with growing concern over an apparent reverse wave of democratic backsliding at the global level. Bridging conceptual approaches and empirical research, this article investigates patterns of democratic backsliding in third-wave democracies. It applies a range of innovative sequence analysis techniques to the Varieties of Democracy dataset to provide a dynamic perspective on the evolution of different types of democratic safeguards against executive expansion. The resulting typology differentiates stable trajectories from different patterns of backsliding and sheds light on the diversity of backsliding processes that diverge in their shape, depth, and timing in respect to initial democratic transition. The findings contribute to broader debates on the nature of democratic backsliding and have important implications both for our theoretical understanding of the phenomenon and the practical responses devised to counter backsliding trends.